Nierenersatzverfahren bei therapierefraktärer Herzinsuffizienz = Renal replacement therapy for refractory heart failure - Schwenger, Vedat; Remppis, Bjoern-Andrew (Der Internist, 2012)
After broad cardiological and nephrological evaluation and consideration of optimal conservative options according to national and international guidelines, renal replacement therapy might be helpful in patients with refractory heart failure even if they are not dialysis-dependent. This is even more important as renal failure is a strong predictor for mortality in patients with severe congestive heart failure (CHF) and CHF is one of the fastest growing morbidities in western countries. Although peritoneal dialysis (PD) is frequently used in patients with CHF its role remains unclear. Acute chronic volume overload in refractory CHF is still an unresolved clinical problem. In patients with acute heart and renal failure with need of management in an intensive care unit, extracorporeal ultrafiltration or a dialysis modality should be preferred. In patients with chronic refractory CHF, volume overload and renal failure, peritoneal dialysis should be the therapy of choice. Due to the limited data available, treatment and outcome parameters should be recorded in the registry of the German Society of Nephrology (http://www.herz-niere.de).